Odpowiedź:
9x + 7 = 3x - 11
9x - 3x = -11 - 7
6x = -18 /:6
x = -3
2(x + 2) = 5(x - 1)
2x + 4 = 5x - 5
2x - 5x = -5 - 4
-3x = -9 /:(-3)
x = 3
1 - (4 - 3x) = 5x + 3
1 - 4 + 3x = 5x + 3
3x - 5x = 3 + 3
-2x = 6 /:(-2)
x = -3
4(3x - 1) - (2x - 1) = x - (7x - 3)
12x - 4 - 2x + 1 = x - 7x + 3
10x + 6x = 3 + 3
16x = 6 /:16
x = 6/16 = 3/8
(4x + 7)/2 = x + 5 + (5x - 1)/6
2x + 7/2 = x + 5 + 5/6x - 1/6
2x - 5 5/6x = 4 5/6 - 7/2
-3 5/6x = 4 5/6 - 3 1/2
-23/6x = 4 5/6 - 3 3/6 /*(-6/23)
x = -6/23(4 2/6) = -6/23 * 4 1/3 = -6/23 * 13/3 = -2/23 * 13 = -26/23 = -1 3/23
wystarczy?
Szczegółowe wyjaśnienie: